Integrasi Kearifan Lokal, Estetika Gerak, dan Sains Olahraga: Standardisasi Gerak Dasar Bela Diri Silat Tradisional Pusaka Rinjani di Lombok NTB - Muhammad Riyan Hidayatulah; I Nyoman Sukartidana; Wahyu Kurnia (Universitas Hamzanwadi, 2026)
The traditional Pusaka Rinjani silat in Lombok faces preservation challenges due to the lack of scientifically grounded standardization of basic movements that remain rooted in local culture, thereby risking the distortion of its philosophical values, aesthetics, and technical effectiveness. This study aims to develop a model for standardizing basic movements that comprehensively integrates local wisdom, movement aesthetics, and sports science. The method used is a qualitative-quantitative interdisciplinary approach with a mixed-methods design, encompassing ethnographic studies, analysis of movement aesthetics (wiraga, wirama, wirasa), and biomechanical measurements using Kinovea 8.0 software on three masters and six senior practitioners. The research results indicate that each basic movement possesses philosophical meaning (religious, balance, solidarity), measurable aesthetic value through posture, rhythm, and emotional expression parameters, as well as efficient and safe biomechanical rationalization (knee angle 124°, punching speed of 5.8 m/s, kicking speed of 6.2 m/s, and blocking reaction time of 0.32 seconds). The conclusion of this study is that the resulting standardization model is holistic, scientific, measurable, and remains rooted in local culture, making it suitable for use as a guideline for training, physical education, and the preservation of Indonesia’s intangible cultural heritage.